Harmed? Harmful? Experiencing Abusive Adult Children With Mental Disorder Over the Life Course. (September 2016) - Band-Winterstein, Tova; Avieli, Hila; Smeloy, Yael
Older parents of an adult child coping with a mental disorder that is expressed by violent deviant behavior face significant parenting challenges. The purpose of this article is to explore the ways older parents exposed to abuse by their adult children with mental disorder (ACMD) perceived their child's violent deviant behavior along the life course. In a qualitative-phenomenological study, 16 parents aged 58 to 90 were interviewed in depth. Three major themes emerged: (a) ongoing total care for the child's needs along the life course, (b) constructions and perceptions of the child through the years—Parents perceived their children over two continua, reflecting their experience of the child's deviant behavior: the child as more harmed versus more harmful, the child as normative versus pathological—and (c) the parent's emotional world toward the harmed–harmful child. The findings enable a deeper understanding of the various ways in which parents cope with living with deviant behaviors of their ACMD. Hence, this study can serve as a framework for developing tailored and differential intervention methods.